Modification of glycidyl methacrylate based block copolymers and their aqueous solution behaviours. (January 2019) - Kocak, Gökhan; Solmaz, Gökhan; Tuncer, Cansel; Bütün, Vural
Graphical abstract: Homopolymer of glycidyl methacrylate and its diblock and triblock copolymers with poly(ethylene glycol)methyl ether and methyl methacrylate were successfully synthesized via atom transfer radical polymerization. Epoxy groups of PGMA blocks were then converted to hydrophilic form by reacting with secondary amines (morpholine, 1-methylpiperazine and diethyl amine) over a ring-opening reaction. This ring-opening reaction caused the formation of hydroxyl and tertiary amine residues on each GMA unit. Tertiary amine residues of resulting derivative block copolymers were further converted to quaternary form with alkyl halides via quaternization reaction. The synthesized derivative polymers had stimuli-responsive nature. They well respond solution pH, temperature and ionic strength. With this study, it is demonstrated that PGMA-containing polymers provide us a great way to prepare different polymeric structures with various stimuli-responsive moieties via multi-step derivative reactions. With this low-cost pathway, by use of the modified PGMA (co)polymers, new stimuli-responsive (co)polymers with various content and architecture can be synthesized. These resulting (co)polymers might be more useful in various applications when compared to polymers that are too abundant in the literature. Highlights: Production of poly(glycidyl methacrylate)-based block copolymers via ATRP chemistry. pH, temperature and ionic strength responsive polymers. Ring-opening reaction of poly(glycidyl methacrylate) with secondary amines. Block copolymer micelles in aqueous solution. Abstract: Poly(glycidyl methacrylate) (PGMA) homopolymer, poly(ethylene glycol)methyl ether- block -poly(glycidyl methacrylate) (MPEG- b- PGMA), poly(methyl methacrylate)- block -poly(glycidyl methacrylate) (PMMA- b -PGMA) diblock copolymers, and poly(ethylene glycol)methyl ether- block -poly(glycidyl methacrylate)- block -poly(methyl methacrylate) (MPEG- b- PGMA- b -PMMA) triblock copolymers with different molecular weights and polymerization degrees were successfully synthesized via atom transfer radical polymerization. Epoxy groups of PGMA blocks were converted to hydroxyl and tertiary amine residues by reacting with secondary amines (morpholine, 1-methylpiperazine and diethyl amine) over a ring-opening reaction. Additionally, derivative (co)polymers containing poly(2-hydroxy-3-methyl piperazinepropyl methacrylate) (PHMPPMA) have also been quaternized with different alkyl and aryl halides. Aqueous solution behaviours of resulting functional polymers including poly(3-diethylamino-2-hydroxypropyl methacrylate) (PDEAHPMA), poly(2-hydroxy-3-morpholinepropyl methacrylate) (PHMPMA), PHMPPMA and its quaternarnized form PQHMPPMA homopolymers and their block copolymers with MPEG and/or PMMA were investigated by varying solution conditions such as pH, ionic strength and temperature. Their solution behaviours were investigated by using proton nuclear magnetic resonance spectroscopy and dynamic light scattering techniques.